eの冪乗の基本

eの冪乗の基本

(1)

\[ e^{\alpha+\beta}=e^{\alpha}e^{\beta} \]

(2)

\[ e^{x+iy}=e^{x}\left(\cos y+i\sin y\right) \]

(1)

\begin{align*} e^{\alpha+\beta} & =\sum_{k=0}^{\infty}\frac{\left(\alpha+\beta\right)^{k}}{k!}\\ & =\sum_{k=0}^{\infty}\sum_{j=0}^{k}C(k,j)\frac{\alpha^{j}\beta^{k-j}}{k!}\\ & =\sum_{k=0}^{\infty}\sum_{j=0}^{k}\frac{\alpha^{j}\beta^{k-j}}{j!(k-j)!}\\ & =\sum_{k=0}^{\infty}\sum_{j=0}^{\infty}\frac{\alpha^{j}\beta^{k}}{j!k!}\\ & =\sum_{j=0}^{\infty}\frac{\alpha^{j}}{j!}\sum_{k=0}^{\infty}\frac{\beta^{k}}{k!}\\ & =e^{\alpha}e^{\beta} \end{align*}

(2)

\begin{align*} e^{x+iy} & =e^{x}e^{iy}\cmt{\text{(1)より}}\\ & =e^{x}\left(\cos y+i\sin y\right) \end{align*}

ページ情報

タイトル

eの冪乗の基本

URL

https://www.nomuramath.com/yp1rdsbv/

SNSボタン